2009
DOI: 10.1051/0004-6361/20077462
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale environment of low surface brightness galaxies

Abstract: Context. The exact formation scenarios and evolutionary processes that led to the existence of the class of low surface brightness galaxies (LSBs) have not yet been understood completely. There is evidence that the lack of star formation expected to be typical of LSBs can only occur if the LSBs were formed in low-density regions. Aims. Since the environment of LSBs has been studied before only on small scales (below 2 Mpc), a study of the galaxy content in the vicinity of LSB galaxies on larger scales could a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 55 publications
7
71
2
Order By: Relevance
“…146]. Both have low metallicities and high gas mass fractions and reside in similar environments [128,134]. If BCGs are bursting, clearly their progenitors must be either irregulars or LSBGs.…”
Section: Gas Contentmentioning
confidence: 99%
“…146]. Both have low metallicities and high gas mass fractions and reside in similar environments [128,134]. If BCGs are bursting, clearly their progenitors must be either irregulars or LSBGs.…”
Section: Gas Contentmentioning
confidence: 99%
“…They also proposed that another galaxy in the area, 350 kpc away from Malin 1 may have interacted with the LSBG 1 Gyr ago. Interactions and companions, however, are not limited to or typical of LSBG that live in less dense environments than their high surface brightness counterparts (Rosenbaum & Bomans 2004;Rosenbaum et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Zackrisson et al 2005;Vorobyov et al 2009), which means that they appear to have a lower metallicity Haberzettl et al 2007), lower star formation rate (O'Neil et al 2007), are evolving much more slowly (van den Hoek et al 2000), have larger gas fraction Schombert et al 2001), lower galaxy density (Rosenbaum et al 2009) and larger amounts of dark matter than what is typically found in normal galaxies.…”
Section: Introductionmentioning
confidence: 99%